MEME INTEGRATION IN ENGLISH WRITING INSTRUCTION - Krisbiantoro, Benny; Soali, Muhammad (JR-ELT (Journal of Research in English Language Teaching), 2023)
The research method for utilizing memes in English writing instruction involves several steps, beginning with the identification and selection of relevant memes aligned with learning objectives. These memes aim to foster creativity and enhance students' comprehension of English content. Following this, writing activities integrated with memes are designed and implemented to stimulate critical thinking and expression in diverse contexts. The method's effectiveness is evaluated by analyzing students' writing quality pre and post-meme incorporation, along with gathering feedback to assess its success in enhancing English comprehension. The findings highlight the significance of meme integration in engaging students effectively, stimulating creativity, and enhancing comprehension. Moreover, the memes consistently prompted improved critical thinking and expression among students in various contexts, contributing to enhanced language proficiency and originality. However, educators should curate memes thoughtfully to ensure relevance and educational value, with ongoing professional development crucial for maximizing the method's potential. In conclusion, meme integration has proven to be a dynamic pedagogical tool, enhancing student engagement, critical thinking, and writing skills, yet necessitating careful curation and continual educator development for its effective implementation.